Deep into the structure of the first galaxies: SERRA views. Issue 2 (21st May 2019) - Pallottini, A; Ferrara, A; Decataldo, D; Gallerani, S; Vallini, L; Carniani, S; Behrens, C; Kohandel, M; Salvadori, S
ABSTRACT: We study the formation and evolution of a sample of Lyman break galaxies in the epoch of reionization by using high-resolution (∼10 pc), cosmological zoom-in simulations part of the serra suite. In serra, we follow the interstellar medium thermochemical non-equilibrium evolution and perform on-the-fly radiative transfer of the interstellar radiation field (ISRF). The simulation outputs are post-processed to compute the emission of far infrared lines ([C ii ], [N ii ], and [O iii ]). At z  = 8, the most massive galaxy, 'Freesia', has an age $t_\star \simeq 409\, \rm Myr$, stellar mass M ⋆ ≃ 4.2 × 10 9 M⊙, and a star formation rate (SFR), ${\rm SFR}\simeq 11.5\, {\rm M}_{\odot }\, {\rm yr}^{-1}$, due to a recent burst. Freesia has two stellar components (A and B) separated by ${\simeq } 2.5\, {\rm kpc}$ ; other 11 galaxies are found within 56.9 ± 21.6 kpc. The mean ISRF in the Habing band is $G = 7.9\, G_0$ and is spatially uniform; in contrast, the ionization parameter is $U = 2^{+20}_{-2} \times 10^{-3}$, and has a patchy distribution peaked at the location of star-forming sites. The resulting ionizing escape fraction from Freesia is $f_{\rm esc}\simeq 2{{\ \rm per\ cent}}$ . While [C ii ] emission is extended (radius 1.54 kpc), [O iii ] is concentrated in Freesia-A (0.85 kpc), where the ratio $\Sigma _{\rm [O\, {\small III}]}/\Sigma _{\rm [C\, {\small II}]}\simeq 10$ . As many high- z galaxies, Freesia lies below the local [C ii ]–SFR relation. We show that this is the general consequence of a starburst phase (pushing the galaxy above the Kennicutt–Schmidt relation) that disrupts/photodissociates the emitting molecular clouds around star-forming sites. Metallicity has a sub-dominant impact on the amplitude of [C ii ]–SFR deviations.